1999
DOI: 10.1177/0306624x99432007
|View full text |Cite
|
Sign up to set email alerts
|

Type III Trauma: Toward a More Effective Conceptualization of Psychological Trauma

Abstract: Research on offenders and crime victims underscores the importance of identifying trauma-related events and treating their effects. The authors build on the work of psychiatrist Lenore Terr, who distinguished Types I and II psychological trauma, by proposing a third category, Type III trauma. Type III trauma occurs when an individual experiences multiple, pervasive, violent events beginning at an early age and continuing over a long period of time. Diagnostic criteria include alterations in memory and consciou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(29 citation statements)
references
References 11 publications
0
27
0
2
Order By: Relevance
“…Therefore, the effects of both SI and ZD observed in this study are considered to be similar to those of such situations. Neglect, particularly during early childhood, is a form of type III trauma; i.e., extreme trauma characterized by multiple traumatic experiences that typically begin at an early age and might be perceived as life-threatening [44]. Traumatic stress caused by childhood neglect compromises homeostasis and leads to a range of long-term biological changes involving the nervous and endocrine systems [45,46].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the effects of both SI and ZD observed in this study are considered to be similar to those of such situations. Neglect, particularly during early childhood, is a form of type III trauma; i.e., extreme trauma characterized by multiple traumatic experiences that typically begin at an early age and might be perceived as life-threatening [44]. Traumatic stress caused by childhood neglect compromises homeostasis and leads to a range of long-term biological changes involving the nervous and endocrine systems [45,46].…”
Section: Discussionmentioning
confidence: 99%
“…For example, while the DSM emphasizes re-experiencing, avoidance, and hyperarousal in response to a discrete event, some youth are exposed to prolonged abuse and neglect at the hands of caregivers (Robertson et al, 2008). As a result, youth may exhibit additional symptoms consistent with complex trauma, which can include alterations in consciousness, self-perception, affect regulation, perception of the perpetrator, relations with others, and systems of meaning (Ford, Chapman, Pearson, Borum, & Wolpaw, 2008;Herman, 1992;Kerig, Moeddel, & Becker, 2011;Soloman & Heide, 1999). Second, youth may be resistant to report exposure to potentially stigmatizing events.…”
Section: Downloaded By [Northeastern University] At 23:22 20 Novembermentioning
confidence: 99%
“…Ordinal logistic regressions showed that children who were exposed to one or more traumatic experiences were more likely to score within a higher range of internalizing and externalizing symptoms than children with no history of trauma. Finally, exposure to community violence was an important predictor of symptomatology beyond the effects of CT.Keywords: Childhood Trauma Questionnaire; complex trauma; early adversity; community violence, trauma assessment.Complex trauma (CT) concerns the consequences of multiple experiences of emotional, physical, or sexual abuse, and emotional or physical neglect at an early age within a caregiving context (Bernstein et al, 2003;Mendelsohn et al, 2011;Solomon, 1999). The effects of CT on psychological development and symptomatology have been extensively studied during the past two decades (Anda et al, 2006;Cummings & Berkowitz, 2014;Dong et al, 2004;Dube et al, 2001;Geffner & Tishelman, 2011).…”
mentioning
confidence: 99%